The LncRNA HOTAIRM1 Promotes Tamoxifen Resistance by Mediating HOXA1 Expression in ER+ Breast Cancer Cells - Kim, Clara Yuri (J Cancer, 2020)
Breast cancer is one of the most commonly diagnosed cancers in women worldwide. Approximately 40% of patients with breast cancer acquire endocrine resistance following therapy with tamoxifen. Many explanations for the development of endocrine resistance have been put forward, one of them being the dysregulation of long non-coding RNAs (lncRNAs). The lncRNA HOTAIRM1, known to be involved in myelopoiesis as well as transcriptional regulation of the HOXA genes in embryonic stem cells, is also expressed in breast cancer cells. This study explored the molecular mechanisms of HOTAIRM1 involved in acquired tamoxifen resistance. We showed that HOTAIRM1 and HOXA1 are concurrently up-regulated in tamoxifen-resistant MCF7 (TAMR) cells. Knockdown of HOTAIRM1 down-regulated HOXA1 expression and restored sensitivity to tamoxifen. In addition, the knockdown of HOXA1 showed similar effects, suggesting that the HOTAIRM1/HOXA1 axis regulates tamoxifen resistance. Furthermore, we showed that HOTAIRM1 directly interacts with EZH2 and prevents the PRC2 complex from binding and depositing H3K27me3 on the putative promoter of HOXA1. Together, our findings suggest that HOXA1 and its neighboring lncRNA, HOTAIRM1, might serve as potential therapeutic targets for ER+ breast cancer patients who have acquired tamoxifen resistance.